Science, Bread, and Circuses : Folkloristic Essays on Science for the Masses - Schrempp, Gregory Allen, 1950- (Utah State University Press, 2014)
"In Science, Bread, and Circuses, Gregory Schrempp brings a folkloristic slant to the topic of popular science, calling attention to the persistence of folkloric form, idiom, and worldview within the increasingly important dimension of popular consciousness defined by the impact of science. Schrempp considers specific examples of texts in which science writers employ folkloric tropes--myths, legends, proverbs, or a variety of gestures from religious tradition--to lend authority or credibility to their message. In each essay he explores an instance of science popularization rooted in the quotidian round: variations of folkloric formulae in monumental measurements, invocations of science-heroes like saints or other inspirational figures, the battle of mythos and logo in parenting and academe; how the meme has become embroiled in quasi-religious treatments of the problem of evil, and a range of other tropes of folklore drafted into the service of exposition of scientific topics. Science, Bread, and Circuses places the relationship of science and folklore is at the very center of folkloristic inquiry in an attempt to rephrase and thus domesticate scientific findings and claims in folklorically-imbued popular forms"--